IDENTITY, CULTURE, AND SECURITY: HUNGARY'S DIFFERING POSITIONS ON MUSLIM AND NON-MUSLIM REFUGEES IN THE 2015 AND 2022 EUROPEAN REFUGEE CRISIS - Trisonia, Lina; Makhroja, Mega Nisfa; Mahmuluddin, Mahmuluddin (Department of International Relations, Universitas Brawijaya, 2024)
The European refugee problem has attracted global attention, especially amid the influxes of people in 2015 and 2022. Hungary, being a member state of the European Union, shown divergent stances towards refugees originating from the Middle East and Ukraine. The purpose of this essay is to examine Hungary's unique position regarding refugees, both Muslim and non-Muslim, during times of crisis, and to clarify the underlying causes behind these positions. This analysis examines how Hungary's attitude to refugees was influenced by cultural identity and national security, using the constructivism theory proposed by Peter J. Katzenstein and the notion of Migration and Security. Research findings suggest that Hungary's position towards Muslim migrants was greatly influenced by unfavourable stigmas connected with Islam and worries regarding national security. Additionally, these beliefs were additionally shaped by the political dynamics and domestic policies of Hungary. This study provides deep insights into the interrelation of identity, culture, and national security in influencing a nation's approach to refugees.Keywords: Refugee Crisis, Muslim Refugees, Non-Muslim Refugees, Hungary